Near-Infrared Quantum Cutting Luminescence and Energy Transfer Mechanism of Ba2Y(BO3 )2Cl:Bi3+, Yb3+ Phosphors - Anjun Huang; Zhengwen Yang; Chengye Yu; Zhuangzhuang Chai; Jianbei Qiu; Zhiguo Song (IEEE Photonics Journal)
The quantum cutting luminescent materials have attracted a great of interest in the fields of solar cells. In this paper, the novel Ba2Y(BO3)2Cl:Bi3+, Yb3+ quantum cutting phosphors were prepared, and their quantum cutting luminescence and energy transfer mechanism were investigated. The visual emission of Bi3+ was observed ranging from 350 to 650 nm, which is attributed to the 3P1→1S0 transition of Bi3+. The near infrared emission ranging from 950 to 1100 nm is due to the 2F7/2→2 F5/2 transition of Yb3+. The cooperative energy transfer mechanism from the Bi 3+ to Yb3+ in Ba2Y(BO3)2Cl:Bi3+, Yb 3+ phosphor was investigated, and their cooperative energy transfer process could be expressed as the Bi 3+(3P1)→Yb3+(2F5/2) + Yb3+( 2F5/2). The maximum quantum cutting efficiency was about 170.2%, which suggested the Bi3+ and Yb3+ co-doped Ba2Y(BO3)2Cl phosphors can act as a promising candidate for the silicon solar cells.